Party Governance and the Selection of Parliamentarians - Klaas J. Beniers (Tinbergen Institute, 2005)
This paper examines the incentives for a party leader in office and for a parties' rank-and-file to replace a sitting member of parliament. As to the leader's decision, we show that the leader prefers to replace a critical member of parliament who votes against the leader's policy. A competent leader designing efficient policies replaces a critical member since the member is unable to evaluate policies. A critical member may also have discovered a policy failure if the leader designs inefficient policies. In that case, the leader infers that the critical member has the ability to learn the quality of policies. An incompetent leader who cares about his reputation rather prefers that the member of parliament is incompetent. To reduce the risk that a future policy failure is discovered, an incompetent leader therefore replaces a critical member and keeps a member who supports the inefficient policy.
Keywords: D72; D78; 330; members of parliament; party governance; political parties; candidate selection; legislative turnover